1994
DOI: 10.3109/10715769409145636
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Peroxidation Product 4-Hydroxynonenal is Formed by - and is able to Attract - Rat Neutrophilsin vivo

Abstract: 4-Hydroxynonenal (HNE), a major aldehydic product of lipid peroxidation, is a chemoattractant for neutrophilic polymorphonuclear granulocytes in vitro. The question was studied, whether HNE is formed during the ingress of neutrophils in the Sephadex model of inflammation. The polydextrane Sephadex G-200, which causes an acute aseptic traumatic inflammation, was injected subcutaneously into rats. The implants were excised 6-36 hours later, and the neutrophils separated from the exsudate by centrifugation. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…It was suggested that either only a certain subpopulation of neutrophils react to HNE, or that the neutrophils, which were derived from pleural exudate, had been desensitized by previous exposure to HNE in vivo. Indeed, HNE was demonstrated to act as a chemoattractant for rat neutrophils in vivo and to desensitize the cells to subsequent HNE exposure [27,28]. In our experiments the number of monocytes responding to HNE was only slightly lower than that for fMLP (78%).…”
Section: Discussionmentioning
confidence: 51%
“…It was suggested that either only a certain subpopulation of neutrophils react to HNE, or that the neutrophils, which were derived from pleural exudate, had been desensitized by previous exposure to HNE in vivo. Indeed, HNE was demonstrated to act as a chemoattractant for rat neutrophils in vivo and to desensitize the cells to subsequent HNE exposure [27,28]. In our experiments the number of monocytes responding to HNE was only slightly lower than that for fMLP (78%).…”
Section: Discussionmentioning
confidence: 51%
“…The cell migration can be evaluated under the light microscope by the leading front technique. The first demonstration of HNE chemotactic power was obtained "in vitro", but afterwards it was confirmed by Schaur et al [20] who carried on "in vivo" experimental researches. They induced an aseptic inflammation in the subcutaneous tissue of a rat leg by injecting in it some polydextrane Sephadex G-200; in control rats they inoculated Sephadex alone, while in the experimental group of rats they inoculated Sephadex together with a solution of preformed HNE.…”
Section: Effects Of Lipid Peroxidation In Inflammationsupporting
confidence: 49%
“…In fact low levels of the lipid peroxidation end products have been shown in tissues even in normal conditions [20]. The rate of the lipid peroxidation can be stimulated by the ROS and the free radicals which can arise also from the normal metabolism of cells.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 4-HNE was capable of activating, at sub-toxic concentrations, VEGF release from ASMC cultures. Interestingly, 4-HNE also stimulated the secretion of IL-8 in macrophages (Facchinetti et al, 2007), lung fibroblasts and epithelial cells (Moretto et al, 2009) as well as eliciting neutrophil recruitment (Schaur et al, 1994). Thus, VEGF might be triggered in chronic cigarette smokers or COPD patients not only by smoke-inhaled acrolein and crotonaldehyde, but also by endogenously formed unsaturated aldehydes such as 4-HNE.…”
Section: Discussionmentioning
confidence: 99%